(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
Literature, a body of written works. The name has traditionally been applied to those imaginative works of poetry and prose distinguished by the intentions of their authors and the perceived aesthetic excellence of their execution. Literature may be classified according to a variety of systems, including language, national origin, historical period, genre, and subject matter.